Analyzing CV/resume using natural language processing and machine learning - Reza, Md. Tanzim; Zaman, Md. Sakib (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.